Methods of forming mathematical representations in preschoolers with mental retardation - Баубек, Арай; Мажинов, Бағдат (Pedagogy and Psychology, 2022)
The article describes the importance of the formation of elementary mathematical concepts in preschoolers with mental retardation and outlines the prerequisites necessary for its proper organization. The optimal methods of mastering the concept of number, the development of the ability to count and the basic rules of its application are also shown. The purpose of the article is to identify difficulties in the number system in children with mental retardation with the rational use of special methods aimed at achieving a successful result. The sides of the organization of these methods are also necessarily integrated. Next, we revealed and analyzed the results of the experiment from a quantitative and qualitative point of view. In the selection of the necessary information, a review of various literature was conducted.The materials of the article are of high value, since specialists-defectologists, other specialists can use the information specified in their work. Specialists can detect the absence of signs of dyscalculia (impaired counting skills) in a child at an early stage on their own.